Discrimination of flax cultivars based on visible diffusion reflectance spectra and colour parameters of whole seeds - Yana Troshchynska; Roman Bleha; Lenka Kumbarová; Marcela Sluková; Andrej Sinica; Jiří Štětina (Czech Journal of Food Sciences, 2019)
Discrimination of yellow and brown seeded flax cultivars was made based on visible (Vis) diffusion reflectance spectra of whole seeds. Hierarchy cluster analysis (HCA) and principal component analysis (PCA) were used for the discrimination. Multivariate analyses of Vis spectra led to satisfactory discrimination of all flax cultivars of this study. The CIE L*a*b* colour parameters were calculated from the diffusion reflectance Vis spectra. The values of L* were in the range of 48.8-53.6 and 62.6-66.0% for brown and yellow seeded cultivars, respectively. Chromatic parameters a* and b* were in the range of 2.8-4.9 and 7.9-16.4%, respectively. A strong linear correlation (R2 = 0.9712) was found between a* and b* parameters for all the flaxseed samples. The L* and a* parameters were sufficient for HCA clustering of the individual flax cultivars.